Child soldiers and distributive justice: addressing the limits of law? - Park, Augustine S. J. (Crime, law and social change, 2010)
This paper discusses the limitations of legal responses to the problem of child soldiery, beginning from the premise that the crime of using child soldiers is comprised of both the recruiter and the recruit. While legal approaches are addressed to the recruiter, because of the dearth of enforcement mechanisms, the protections established in international law have failed to prevent the recruitment of under-aged combatants. It remains to be seen how efficacious a deterrent the precedent-setting recent and on-going prosecutions of recruiters will be. Nonetheless, legal approaches do not address the recruit, and thus they fail to account for the complex of social reasons that prompt many children to join armed groups "voluntarily". This paper argues that the conditions that lead children to join armed groups are structural and, thus, must be addressed structurally through developing greater "distributive justice".